Navigating the dreamscape: Examining the reliability of dream interpretations/ Farah Syuhada Mohd Fauzi ... [et al.] - Mohd Fauzi, Farah Syuhada; Muhamad Yusri, Nur Amalia Yusrina; Mohd Nordin, Nordiana; Mohd Ali, Rabiah (Universiti Teknologi MARA, Perak, 2024)
This paper delves into the fascinating and mysterious world of dreams, exploring their significance through a variety of cultural, historical, and philosophical lenses. At the heart of our study are the Kitab Ta'bir Mimpi Manuscripts, a cornerstone of Malay tradition, which offer profound insights into the ancient practice of dream interpretation. By examining the historical context and cultural relevance of these manuscripts, the study aims to uncover the foundational principles that have guided Malay dream symbolism for centuries. The research not only evaluates the dependability of these traditional interpretations but also enriches them by drawing on the wisdom of scholars, philosophers, and other historical sources. This allows us to illuminate the diverse meanings and symbolisms that dreams have held in different cultural settings. Furthermore, by juxtaposing these traditional interpretations with contemporary psychological theories on dreaming, the study strives to bridge the gap between age-old wisdom and modern scientific inquiry. Ultimately, the study provides a comprehensive exploration of how dreams have been understood and interpreted across time, cultures, and intellectual traditions, offering a deeper understanding of this enigmatic aspect of human experience.